PENGARUH JENIS ACTIVATED FLUX DAN VARIASI KUAT ARUS PADA PENGELASAN A-TIG DISSIMILAR MATERIAL TERHADAP KEDALAMAN PENETRASI, KEKERASAN, STRUKTUR MIKRO DAN LAJU KOROSI - Imam Khoirul Rohmat; Moch Iqbal Ramadhan; Dika Anggara (Jurnal Teknologi Terapan, 2022)
The TIG welding process has shallow penetration. The addition of activated flux can increase the depth of penetration of the weld, which is called A-TIG welding, so this study to analyze the effect of the activated flux type and current on the depth of penetration, hardness, microstructure, and corrosion rate. This study used SUS 304 and A36 materials with a thickness of 6 mm which are welded using the A-TIG welding process with variations of activated flux Fe2O3, Cr2O3 and variations in the current strength of 100 amperes and 120 amperes. To find out the results of these variations, this study was tested by macro, hardness, microstructure, and corrosion rate tests. The results of the study on variations in the type of activated flux and variations in current resulted penetration depth of 3.6 mm found in activated flux Cr2O3 with 120 amperes and penetration depth in activated flux Fe2O3 with a value of 2.43 mm on 100 amperes. Then the highest hardness value was found in activated flux Fe2O3 and 120 amperes with a value of 471.48 HVN, and the lowest is in Cr2O3 ampere 100 with a value of 398.16.HVN. The micro test results in a phase change from pearlite, ferrite, and austenite to martensite in the weld metal. And to test the corrosion rate on activated flux Fe2O3 and a current of 120 amperes with a value of 0.24931 mm/year, the activated flux Cr2O3 and a current of 100 amperes with a value of 0.090114 mm/year.